Improvement Of Clean Field With The Implementation Of Medan City Regional Regulation No. 3 Of 2014 Regarding A No-Smoke Area In Medan City - Eddy, Triono (International Journal of Educational Research & Social Sciences, 2022)
Currently, cigarettes are one of the products with a relatively high level of consumption in the community. The problem of smoking is also still a national problem and efforts to overcome it are prioritized because it involves various aspects of problems in life, namely economic, social and political aspects and especially health aspects. Data on the tobacco epidemic in the world according to the World Health Organization (WHO) shows that 1 death due to tobacco worldwide occurs every 6 seconds. Deaths due to tobacco in 2005 were recorded at 5.4 million people and during the 20th century, there were 100 million deaths due to tobacco. If this is allowed, there will be 8 million deaths in 2030 and it is estimated that 1 billion people will die from tobacco during the 21st century. By 2030, It is projected that 80% of tobacco-related deaths occur in developing countries. Medan City Government stipulates Medan City Regional Regulation No. 3 of 2014 concerning Smoking-Free Areas to support the creation of a smoke-free environment so that the City of Medan can be protected from the negative impacts of smoking. Therefore, this research focuses on the process of implementing the Medan City Regulation No. 3 of 2014 concerning Non-Smoking Areas in Medan City in several places by Article 7 to Article 15 of Medan City Regulation No. 3 of 2015. The aim is to see to what extent the Medan City Regulation No. 3 of 2014 concerning Non-Smoking Areas is implemented by the community, government, and law enforcement. The locations that were targeted as well as research locations were 3 schools in Medan, Amplas Terminal, Medan Mayor's Office, and Medan City DPRD. The research method used is descriptive qualitative by collecting primary and secondary data through interviews, direct observation, and recording documents. The data that has been obtained is then analyzed descriptively qualitatively.